Re-analysis of a Genome-Wide Gene-By-Environment Interaction Study of Case Parent Trios, Adjusted for Population Stratification - Ratnasekera, Pulindu; McNeney, Brad (Frontiers in Genetics, 2021)
We investigate the impact of confounding on the results of a genome-wide association analysis by Beaty et al., which identified multiple single nucleotide polymorphisms that appeared to modify the effect of maternal smoking, alcohol consumption or multivitamin supplementation on risk of cleft palate. The study sample of case-parent trios was primarily of European and East Asian ancestry, and the distribution of all three exposures differed by ancestral group. Such differences raise the possibility that confounders, rather than the exposures, are the risk modifiers and hence that the inference of gene-environment (G× E) interaction may be spurious. Our analyses generally confirmed the result of Beaty et al. and suggest the interaction G× E is driven by the European trios, whereas the East Asian trios were less informative.